Efficient production of biodiesel with electric furnace dust impregnated in Na2CO3 solution. (1st January 2022) - Wang, Yi-Tong; Gao, Di; Zeng, Ya-Nan; Li, Jun-Guo; Ji, Ai-Min; Liu, Tian-Ji; Cai, Shuang; Cong, Wen-Jie; Wang, Fu-Ping; Yu, Qing; Wang, Xiao-Man; Fang, Zhen
Abstract: Solid catalyst (Na2 CO3 @EFD) was prepared by wet impregnation of electric furnace dust (EFD) in aqueous Na2 CO3 solution. It had high basicity and acidity of 0.34 and 0.16 mmol/g for biodiesel production. High biodiesel yield of 99.8 wt% from soybean oil was obtained under the optimized reaction conditions (by Central Composite Design) of 71 °C in 111.36 min with 5.4 wt% catalyst and methanol/oil molar ratio of 11.8/1. After 11 cycles, biodiesel yield still maintained at 90.8 wt% with catalyst recovery rate >90 wt% by magnetic separation of catalyst EFD powders (containing Fe3 O4 with magnetism of 59.1 Am 2 /kg). Pure Na2 CO3 particles presented poorer recyclability with lower biodiesel yield of 89.5 wt% even at the eighth cycle by centrifugal separation. Na2 CO3 @EFD catalyst had high activity and recyclability because: (i) EFD as support hosted nanoparticles of Na2 CO3 (30.3 nm) as main base site for transesterification; (ii) porous EFD support provided acidic sites from metal oxides (e.g., ZnO and Al2 O3 ) for esterification; (iii) EFD adsorbed active components into its micropores to maintain high recyclability; and (iv) EFD magnetism from magnetic Fe3 O4 kept high efficient magnetic separation. Total metals in the blended biodiesel met the National Standard of China and heavy metals were lower than typical petrochemical diesel. The study gave a practical use of industrial solid waste for the green production of biodiesel. Graphical abstract: Image 1 Highlights: Nanocatalyst was synthesized by impregnating electric furnace dust in Na2 CO3 solution. It was bifunctional with high basicity and acidity of 0.34 and 0.16 mmol/g. High biodiesel yield of 99.79 wt% was obtained at 71 °C. 90.84 wt% biodiesel yield was still achieved after 11 cycles. Metals in biodiesel met National Standard, lower than that petrochemical diesel.